Return to work after lumbar disc herniation surgery: an occupational cohort study - Laasik Raul; Lankinen Petteri; Kivimaki Mika; Neva Marko H; Aalto Ville; Oksanen Tuula; Vahtera Jussi; Mäkelä Keijo T (TAYLOR & FRANCIS LTD, 2022)
Background and purpose - Lumbar disc herniation is a common surgically treated condition in the working-age population. We assessed health-related risk factors for return to work (RTW) after excision of lumbar disc herniation. Previous studies on the subject have had partly contradictory findings. Patients and methods - RTW of 389 (n = 111 male, n = 278 female; mean age 46 years, SD 8.9) employees who underwent excision of lumbar disc herniation was assessed based on the Finnish Public Sector Study (FPS). Baseline information on occupation, preceding health, and health-risk behaviors was derived from linkage to national health registers and FPS surveys before the operation. The likelihood of RTW was analyzed using Cox proportional hazard univariable and multivariable modelling. Results - 95% of the patients had returned to work at 12 months after surgery, after on average 78 days of sickness absence. Faster RTW in the univariable Cox model was associated with a small number of sick leave days (< 30 days) before operation (HR 1.3, 95% CI 1.1-1.6); high occupational position (HR 1.6, CI 1.2-2.1); and age under 40 years (HR 1.5, CI 1.1-1.9). RTW was not associated with sex or the health-related risk factors obesity, physical inactivity, smoking, heavy alcohol consumption, poor self-rated health, psychological distress, comorbid conditions, or purchases of pain or antidepressant medications in either the univariable or multivariable model. Interpretation - Almost all employees returned to work after excision of lumbar disc herniation. Older age, manual job, and prolonged sick leave before the excision of lumbar disc herniation were risk factors for delayed return to work after the surgery.